Comparative study of functional and radiological outcomes of the usage of two devices, derotation type cephalomedullary nail and the helical blade type in unstable intertrochanteric fractures in the geriatric population at a tertiary-level center - Prakash, Vishal; Singh, Neelu; Gupta, Govind Kumar; Prabhat, Vinay (International Journal of Research in Orthopaedics, 2023)
Background: Intertrochanteric fracture is a common osteoporotic fracture among elderly populations in an aging society. Early surgical fixation on these aging patients has been proposed recently for early rehabilitation and has had a positive impact on reducing comorbidities. For unstable fractures, intramedullary implants generally present biomechanical advantages over their extramedullary counterparts. Methods: The study was a 2 years prospective comparative study from 1st December 2020 to 1st December 2022 conducted in the department of orthopaedics, Rajendra institute of medical sciences, Ranchi, Jharkhand, India. Total number of patients were 50, PFN done in 25 cases and PFN-A2 in another 25 cases. Results: Mean age is 64.4 years in PFN group as compared to 67.3 years in PFN-A2 group. PFN-A2 was done in 84% male while PFN in only 76 % male and in both groups right side was mostly affected. Average surgery time, amount of blood loss, average number of C-arm shoot was more in PFN group. Conclusions: In this study of 50 patients, 25 treated by PFN and 25 by PFN-A2, it was concluded that PFN-A2 was a better construct to treat patients of older age group having osteoporosis because here reaming was not done and helical blade was inserted by hammering which caused compaction of bones in head and neck region.